E-learning for Managing Lesson in Pandemic Era in SMA 2 Lubuk Sikaping - Muhammad Subhan; Dina Fitria; Yusmet Rizal; Heru Maulana; Defri Ahmad; Suherman Suherman; Saddam Al Aziz (Fakultas MIPA Universitas Negeri Padang, 2020)
School atmosphere in pandemic era mostly different with the normal one. An alternative to ensure learning process done by using online learning. But many teacher was not familiar with this type of learning approach. It is an extraneous because teacher never used it before. By workshop supported by devotee, teachers design an alternative. Some free software discuss during socialization, they are edmodo for moving offline class into virtual class, wonderful filmora for creating and editing video, quizzes and kahoot for quiz. The workshop is categorized success, based on teachers' respon which is collected using open questionnaire in every meetings.